PENGARUH MOTIVASI KERJA DAN STRES KERJA TERHADAP KINERJA GURU DI SMPN 2 PAJANGAN - Yunita Fitri Wahyuningtyas; Lusi Feptiasari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine the effect of work motivation and work stress on teacher performance at SMPN 2 Pajangan. Data from the questionnaire research distributed through soft files were tested for validity using correlation and reliability using Cronbach Alpha. The data analysis technique used SPSS version 16 software. The results of this study indicate that together, the work motivation variable and the work stress variable with a significance value of 0.000 and the Fcount result of 9.770 which indicates that all variables have a positive and significant effect on teacher performance at SMPN 2 Displays. Partially, the work motivation variable with a regression significance value of 0.000 which is smaller than a 0.05 significance confirms that there is a positive influence on teacher performance at SMPN 2 Pajangan. This is also seen from the t-count value of 4.234 which is greater than the t-table of 2.015. So it can be concluded that the work motivation variable has a positive effect on teacher performance at SMPN 2 Pajangan. Then the Job Stress variable with a regression significance value of -0.282 which is greater than a significance of 0.05 confirms that there is a negative effect on teacher performance. This is also seen from the t-count value of -.282 which is smaller than the t-table of 2.015. So it can be concluded that the work stress variable has a negative effect on teacher performance at SMPN 2 Pajangan.